If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(3y + 6) = 0 Reorder the terms: -4(6 + 3y) = 0 (6 * -4 + 3y * -4) = 0 (-24 + -12y) = 0 Solving -24 + -12y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + -12y = 0 + 24 Combine like terms: -24 + 24 = 0 0 + -12y = 0 + 24 -12y = 0 + 24 Combine like terms: 0 + 24 = 24 -12y = 24 Divide each side by '-12'. y = -2 Simplifying y = -2
| 6y-3=45 | | 5(6x+6x)=-4 | | x^4-2401=0 | | 180=(x-47)+x | | -9+6x-2x=1-6x | | 10-x=24 | | 10z+8=12+10z | | 2-7x=7-7x-x | | 180=(x-47)+47 | | 4x-1=4x+1 | | -8v+5v=-12-5v | | 17/5=-7x+5+5 | | 16.95+0.05m=22.95+0.02m | | a-6=-5a-12 | | 9(9x+6)=7 | | 3-7c=-7c+17 | | 10minusa=12 | | 5(x+y)-3(x-y)= | | 3(7x+6)=2x | | 11b+6=-27 | | 3n-8n=-6n-3 | | 5(x+y)-5(x-y)= | | 3+7x-5x=-9 | | 5+c=6 | | 10g+3=5g-27 | | x+8=-10-8x | | 6+3-1= | | -5(4x-2)=2(3+6x) | | 8+b=16 | | 4y-12=-12+4y | | 7-5(5a-4)=6-4a | | -6k-7k= |